Uso de paredes vivas na qualidade do ambiente interno: estudo de caso em sala de aula na cidade de Santa Maria - RS - Ribeiro, Luciana Rocha (2020)
The use of vegetation as a bioclimatic strategy in the built environment is widely recognized for the benefits related to thermal comfort, a characteristic arising from the use of vegetation in the urban environment, both in isolation and integrated with the building. However, the use of plant species also offers benefits to users of indoor environments, such as air purification, environmental comfort and maximization of wellbeing. Currently, we spend most of our time indoors. Thus, this strategy also adds to the architectural project the concept of biophilia, inherent human inclination to affiliate with nature, fundamental to physical, mental health and people's well-being. In general, the quality of the internal environment refers to the degree of efficiency and comfort experienced by individuals in interior buildings. The use of vegetation as an air qualifier in the indoor environment has been studied since the 1970s, however studies on the use of vertical gardens indoors are recent and sometimes limited to hermetically sealed chambers. In this context, there are few studies applied in real situations related to the quality of the internal environment and the use of vertical gardens. This work aimed to evaluate the benefits related to the well-being, comfort and air quality provided to students / users of a classroom through the insertion of living walls in this environment. From an experimental point of view, the research was carried out between February and November 2019 (including the production of seedlings, planting in modules, implementation of vertical gardens and data collection), in the D2 classroom of the 3rd grade of the high school of the College Polytechnic of the Federal University of Santa Maria.In this study, two plant species were used, Arachis repens (peanut-forage), a plant native to Brazil (widely used in vegetated cover) and Chlorophytum comosum (chlorophyte), recognized as a species that removes volatile organic compounds. The multi-method approach used in environmental perception studies was adopted as a methodology, listing identification of users' perception and measurement of parameters as research methods, using the tools for data collection: application of questionnaires, measurement of chemical and physical parameters (concentration of carbon dioxide, temperature and relative humidity), photographic survey and application of test preference. This research demonstrated, in general, that the use of vertical gardens brought benefits to users, qualifying the school's internal environment. Among the species used, the peanut-forage showed better results in terms of the students' perception analysis and the measured parameters of carbon dioxide concentration and relative humidity.